The Prophet's Style Learning Method: Prophetic Learning in English Language Teaching (ELT) to Students - Nur Fitria, Tira (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2024)
This research describes the prophet's style learning method and prophetic learning in English Language Teaching (ELT). This research is a library research. The researcher uses sources from books and national journals. The analysis shows that in Indonesia, teaching English is a lifelong endeavor, starting from elementary school and continuing through university. The Prophet Muhammad SAW is a role model for Muslims, as he pioneered education and developed learning models applicable in various contexts, including English study. Teachers/lecturers should prioritize sincerity, patience, and honesty in the classroom to create strong relationships with students and maintain a strong connection with Allah SWT. Prophet Muhammad is a Muslim trendsetter, demonstrating cognitive and affective learning methods. To incorporate prophetic learning into English teaching, they can use prophetic learning strategies such as 1) teacher as a model, 2) stimulus-response/questioning, 3) storytelling, 4) analogy/logical order, 5) direct practice, 6) applied materials, 7) offering advice, 8) closing statement. Prophets possess virtuous qualities such as honesty, trust, communication, and intelligence. Besides, teachers/lecturers should give examples, play the role of guides, and support students in learning progress. Teachers/lecturers should also be able to create curiosity and enthusiasm about the next meeting and be prepared to answer questions and provide answers. In conclusion, prophetic learning is a crucial aspect of a student's life, and educators should emulate the learning methods to ensure their students are equipped with the necessary skills to succeed in their studies.